The mechanisms of HIF-2α action in the carotid body - Prange-Barczyńska, M (2022)
The carotid body (CB) is an arterial chemoreceptor central to ventilatory adaptations to reduced oxygen arterial pressure (hypoxia) and responds both rapidly, by increasing ventilation within seconds of the drop in O2 saturation, and chronically, by potentiating the acute hypoxic ventilatory response (HVR), which is associated with CB hyperplasia. Mechanisms behind these adaptations are not fully understood, but the Hypoxia Inducible Factor (HIF) signalling pathway has been implicated in mediating the CB chronic response to hypoxia. Indeed, HIF-2α isoform has been found to be very highly expressed in the CB.